Reporting the impact of inferior vena cava perforation by filters. (August 2014) - Wood, Emily A; Malgor, Rafael D; Gasparis, Antonios P; Labropoulos, Nicos
Background: Perforation of the inferior vena cava by filters struts is a known complication. The goal of our review is to assess the impact of inferior vena cava perforation by filters based on an open, voluntary national database. Methods: We reviewed 3311 adverse events of inferior vena cava filters reported in Manufacturer and User Facility Device Experience database from January 2000 to June 2011. Outcomes of interest were incidence of inferior vena cava perforation, type of filter, clinical presentation, and management of the perforation, including retrievability rates. Results: Three hundred ninety-one (12%) cases of inferior vena cava perforation were reported. The annual distribution of inferior vena cava perforation was 35 cases (9%), varying from seven (2%) to 70 (18%). A three-fold increment in the number of adverse events related to inferior vena cava filters has been noted since 2004. Wall perforation as an incidental finding was the most common presentation ( N  = 268, 69%). Surrounding organ involvement was found in 117 cases (30%), with the aorta being the most common in 43 cases (37%), followed by small bowel in 36 (31%). Filters were retrieved in 97 patients (83%) regardless of wall perforation. Twenty-five (26%) cases required an open procedure to remove the filter. Neither major bleeding requiring further intervention nor mortality was reported. Conclusions: Inferior vena cava perforation by filters remains stable over the studied years despite increasing numbers of adverse events reported. The majority of filters involved in a perforation were retrievable. Filter retrieval, regardless of inferior vena cava wall perforation, is feasible and must be attempted whenever possible in order to avoid complications.